Defining the Minimal Clinically Important Difference and Patient Acceptable Symptom State for Microfracture of the Knee: A Psychometric Analysis at Short-term Follow-up. Issue 4 (March 2020) - Chahla, Jorge; Kunze, Kyle N.; Tauro, Tracy; Wright-Chisem, Joshua; Williams, Brady T.; Beletsky, Alexander; Yanke, Adam B.; Cole, Brian J.
Background: Several studies have investigated failure rates and magnitude of improvement in patient-reported outcome measures after microfracture surgery for focal chondral defects of the knee; however; what constitutes clinically significant improvement in this patient population is poorly understood. Purpose: To (1) establish the minimal clinically important difference (MCID) and patient acceptable symptom state (PASS) thresholds for microfracture surgery including the time-dependent nature of these thresholds and (2) identify predictors of achieving the MCID and PASS in patients specifically undergoing microfracture of the knee. Study Design: Case series; Level of evidence, 4. Methods: A secure institutional cartilage preservation repository was queried for all patients who underwent microfracture between 2004 and 2017. The distribution method was used to calculate MCID thresholds for the International Knee Documentation Committee (IKDC) score and the Knee injury and Osteoarthritis Outcome Score (KOOS), whereas an anchor-based method was used for the PASS. Multivariate logistic regressions were constructed to determine predictors of achieving the MCID and PASS. Results: A total of 206 patients with a mean ± SD age of 33.7 ± 13.2 years and body mass index of 26.9 ± 5.3 kg/m 2 were included. All thresholds for the MCID and PASS increased over time except for the MCID thresholds for the KOOS Sports and Symptoms subscales. The proportion of patients who achieved the MCID (6 months, 78.4%; 12 months, 83.9%; 24 months, 88.6%) and PASS (6 months, 67.7%; 12 months, 79.2%; 24 months, 76.1%) generally increased over time. Older age and larger lesion size were negative independent predictors of MCID achievement. Older age was also a negative predictor of the PASS, whereas male sex and higher preoperative KOOS Symptoms and Pain scores were positive independent predictors of the PASS. Conclusion: The MCID and PASS thresholds for the IKDC and KOOS in patients undergoing microfracture of the knee are dynamic, with an increasing number of patients achieving the MCID over time. The percentage achieving the PASS increased between 6 and 12 months and then declined slightly at 24 months. Independent predictors of achieving the MCID were lesion size and age at surgery, whereas predictors of achieving the PASS included lesion size, male sex, and greater preoperative KOOS Symptoms and Pain scores.